Entre éthique de l’intégration et pratiques de la différenciation : (re)penser l’organisation du travail scolaire ? - Olivier Maulini; Cynthia Mugnier (Recherches en Éducation)
Compulsory schooling values and aims for student integration, however, educators are required to consider each student individually in order to achieve this goal, thus risking an enduring divide in destinies. How can one prevent this paradox? Our reasoning on the subject is threefold. First, one needs to take into account the origin of traditional school organization which organizes students into somewhat specific groups according to their needs and/or difficulties. Second, one must demonstrate that history influences, not only pedagogical practices, but also the perceived difficulties encountered, which in turn can encourage innovative practices. Third, one must take into consideration the results of research on school organization during the primary years learning cycles. When teaching teams decide to modify, or rethink, links between internal and external differentiation of student progress, the following questions must be considered. What developments can be expected? What are the resulting cognitive conflicts? Which differentiation modifications are to be adopted and how are they put in place?